MATCHING THE EMOTION EVOKED FROM A VIDEO ADVERTISEMENT WITH THE BRIEF: CASE STUDY DOVE VIDEO ADVERTISEMENT - Putra, Falih Hermon; Iskandar, Budi Permadi (Journal of Business and Management, 2018)
Abstract. Fast moving consumer goods products especially soap sold very quickly in the market and cannot be separated with our life. we often choose one brand without further consideration because we are already familiar with the brand. we all made to believe there is different type of soap such as soap for family, for women, and men. Soap offered the same function one with another, which is to clean your body. It doesn’t matter whether you are a man or women. These perceptions are created through an advertisement that the brand does. So, brand offer not only the function but also the emotions. Video become one of the most effective channels to deliver message. Video can deliver emotions and entertain the audiences. Company spend a lot of money to make excellent video and usually cooperates with agency. This is why we have to assure the money spent will give a desire result. evaluating the effectiveness of video seems necessary since it can deliver message to customer.to know the effectivity, we can compare the planned emotion with the perceived emotion by the audiences. So, we know whether the video has successfully delivered the message or not. This study uses a qualitative approach. A semi-structured interview used as a way to collect data. The data is analyzed using the coding method. Respondents were given some questions about their perception after watching Dove’s video advertisement. The findings of this research show the most positive emotions and negative emotions evoked in the video. This study finds objects that stimulate the emergence of an emotion. The results of the analysis provide a new perspective on people's emotions in the reactions of video advertisement. Consequently, it helps marketers to create advertising videos that can emotionally bond them to their target audience.Keywords: Emotion Evoke, Dove, Marketing, Video Ads, People perception